Pengaruh Model Pembelajaran Project Based Learning (PjBL) terhadap Kemampuan Pemecahan Masalah pada Materi Pokok Bangun Datar Siswa Kelas IV SDN 03 Paokmotong Tahun Ajaran 2025/2026 - Yogi Septian Hadi; Lalu Sirajul Hadi; Baiq Yuni Wahyuningsih (Mataram University, 2026)
This study was motivated by the low mathematical problem-solving ability of fourth-grade students on plane geometry topics, particularly the perimeter and area of squares, rectangles, and triangles. This study aimed to determine the effect of the Project Based Learning (PjBL) model on the mathematical problem-solving ability of fourth-grade students at SDN 03 Paokmotong. This research employed a quantitative approach using a quasi-experimental method with a posttest-only control group design. The research sample consisted of 50 fourth-grade students from SDN 03 Paokmotong. Data were collected through a mathematical problem-solving test and classroom implementation observation. The research instruments included a mathematical problem-solving test and an observation sheet for the implementation of the learning process. Data were analyzed using descriptive statistics to determine the mean and standard deviation, the Kolmogorov–Smirnov normality test, the Fisher homogeneity test, and hypothesis testing using the Independent Samples t-test. The results showed that the mean score of the experimental class was 78.68, which was higher than that of the control class, which was 62.56. The hypothesis test results indicated that the calculated t-value (tcount = 5.19) was greater than the critical t-value (ttable = 2.01) at the 0.05 significance level; therefore, H₀ was rejected and H₁ was accepted. It can be concluded that the Project Based Learning (PjBL) model has a significant effect on the mathematical problem-solving ability of fourth-grade students at SDN 03 Paokmotong in learning plane geometry.